VEGETATIVE PROPAGATION OF ESPIRRADEIRA BY CUTTINGS - da ROCHA, Silvana Cruz; QUISEN, Regina Caetano; de QUEIROZ, José Antonio Leite; ZUFFELLATO-RIBAS, Katia Christina (Scientia Agraria, 2004)
In order to study the vegetative propagation for Nerium oleander, a shrub used in arborization, three different varieties were carried out several root cuttings experiments with different concentrations of IBA. Although there had not been significant differences between the concentration of IBA, the rosa simples variety presented greater percentage of rooting, number and largest roots in all applied treatments (0, 1000 and 2000 mg.L-1), while that the same concentrations of IBA in the branca variety presented a smaller percentage of rooting compared to the control. In rosa dupla variety was observed that the cuting treateds with 1000 mg.L-1 induced few roots (36,7%).